THE EVOLUTION OF RELIGIONS: A HISTORY OF RELATED TRADITIONS. - Saidl, Michal (Religious Studies Review (John Wiley & Sons, Inc.), 2025)
This text focuses on a monograph by a curatorial scientist at the Field Museum of Natural History that applies evolutionary theory and phylogenetic trees to examine the historical diversification and interrelationships of the world’s organized religions in an agnostic framework. The book is structured into twelve chapters covering the application of evolutionary processes to religion, the development and interaction of major religious systems and their components, and concludes with a call for openness to ideological and cultural diversity for human survival. Supplementary materials such as a glossary, notes, and references support the text, which is richly illustrated to aid understanding. The work is intended for both scholars in religious studies and related fields, as well as general readers interested in religion and human culture.